PUBLIC POLICY AS A SYSTEM OF UTILIZING THE POTENTIAL OF NON-GOVERNMENTAL ORGANIZATIONS - Tokar, Marian (Theory and Practice of Public Administration, 2019)
The realities of today are under the pressure of profound transformations of public-management relations both in the world and in Ukraine, where the role of public policy changes in the format of the dynamics of the political regime and forces it to adapt its functional features to public inquiries. Based on such interaction, public policy, by improving the democratic practice of relations between the state and civil society, acquires a new quality in order to realize the synergistic goals of all those interested in the development of the state. In this case, public policy acquires the characteristics of a system that can use the measures of realization of interests of the state and society through the perspective use of the potential of non-governmental organizations. The purpose of the article is to try to update the attention on the evolution of public policy as a comprehensive system of measures to realize the interests of the state and society by harnessing the considerable potential of public organizations. The use of this type of public associations as an organization of socially useful action, in our opinion, will contribute to the synergistic effect of modern Ukrainian state-building. Today, the Ukrainian state, in the sense of understanding it as a democratic political institute, possesses a considerable number of effective public-administrative parameters, as well as structural and functional characteristics and various factors of influence, which are interconnected and closely interact with each other. In order to make rational use of the potential of existing phenomena and processes, as well as to constantly optimize state-public relations, a comprehensive, systematic analysis of the process of national state formation is envisaged through public-management innovations and the use of the potential of publicly-useful non-governmental organizations that offer their services as service providers. In this systematic unity, in our opinion, it is necessary to explore the prospects of all interrelated elements of the public-state organism. Therefore, a systematic approach in this context is a starting point in the study of the multifaceted nature of public policy as a set of basic directions and ways of activity of the state, in particular, oriented towards the development of civil society and the development of its essence in the public sphere. Based on the awareness of the close interaction of the state and civil society towards achieving a synergistic effect for their development, the practice of using qualitative public policy features helps to realize the interests of all citizens, including through effective involvement in the cooperation of non-governmental organizations. Their potential has the potential to become an auxiliary resource in achieving state-building goals. The positive consequence of this depends on the specific calculations of the authorities on the effectiveness of the use of public-management innovations in public-utility activities of non-governmental organizations, on the clarification and constructive complement of the legal framework of their functioning and mutual desire of the parties to cooperate for the sake of building a stable, social justice.